1630 Laparoscopic Repair of Linea Arcuata Hernia Presenting as Generalised Abdominal Pain - a Case Report. (12th October 2021) - Sayers, A; Ain, Q; Thomas, R; Laliotis, A
Abstract: Background: Arcuate line hernia (LAH) is an abnormal ascending herniation of intraperitoneal structures over the linea arcuate, between the rectus abdominus muscle and the posterior layer of its sheath. It is a rare clinical entity often associated with non-specific abdominal pain, posing a significant diagnostic challenge. The true prevalence is unknown, and diagnosis is almost always radiological. Case Report: We report the case of a 57-year-old lady investigated extensively for frequent episodes of generalised abdominal pain. No palpable hernial defect or other pathology was identified on clinical examination. Subsequent computed tomography(CT) of the abdomen and pelvis revealed a 95 x 74 mm arcuate line hernia(LAH) anterior to the transversalis fascia, containing small bowel loops. She underwent an elective laparoscopic repair involving closure of the hernial defect with 2-0 knotless barbed sutures and reinforcement with a 20 x 15 cm underlay mesh. Postoperative recovery was uneventful, with complete resolution of her symptoms. One year after the repair there were no signs of recurrence. Discussion: To our knowledge, only eleven prior cases of symptomatic LAH have been reported in the literature. There is no conclusive evidence regarding most appropriate diagnostic imaging, treatment approach and follow up regimen. Clinical diagnosis is difficult. Existing literature suggests use of CT scan as the primary imaging modality for diagnosis. The laparoscopic approach is safe, feasible and has certain advantages. This includes confirmation of diagnosis, excludes the presence of concomitant hernias and enables inspection of herniated viscera. Prosthetic mesh reinforcement is considered to minimise recurrence. Long term follow-up of these patients is required